Epistemologic review of new urban typologies for the identification of mini cities in Central America - Acosta Schnell, Sabrine (2017)
Central American mini cities are new urban typologies that can be identified as mixed-use projects with residential, commercial and entertainment spaces of private initiative. The novelty of this urban typology suggests an approach from the urban geography since it has not been previously investigated. This is the main objective of this epistemological review of the  approaches of urban typologies like gated communities, commercial centres and “Theme parks” to try to characterize the Central American mini cities. This bibliographic review is part of a doctoral thesis that addresses the issue specifically for the Costa Rican and Guatemalan cases. The bibliographic review was not intended to be exhaustive or thorough, but critical and  diagnostic. Six main themes are identified. These include discussions on the risk of simplifying the theory of urban typologies to the entire American continent. Also, several productions used a wide historical cut from the antiquity to the current trends. Another line is the search for the definition of city to adapt it to the current proposals of mini cities. There is also research on malls and theme parks that emulate mini cities. Another recurring theme is the constant reorganization of urban space and its constant dynamic character. Finally, gaps were identified in the theory of urban geography in Central America, specifically on the recent mini-cities. It is concluded by reflecting on the need to provide a specific analysis on mini cities as new  urban typologies in Central America.